Microbial Prevalence and Antimicrobial Sensitivity in Dairy Animals Suffering From Purulent Vaginal Discharge - Singh, Gyan; Yadav, Ritu; Kumar, Sandeep; Hitesh; Pandey, Anand Kumar (The Indian Journal of Animal Reproduction, 2022)
Uterine infection can be diagnosed by taking a swab from fornix vagina or directly from cervix and can be used for cytology and microbiological evaluation. In this study, vaginal swabs for culture and sensitivity test were obtained from 20 buffaloes and two cows which were shedding purulent pus discharge from their reproductive tract. The most isolated microorganism was Escherichia coli which were detected in 17 animals, followed by Staphylococcus spp. and Streptococcus spp. which was detected in 15 and 14 animals, respectively. Klebsiella spp and Baccilus spp. were diagnosed in two animals whereas; Psuedomonas spp. and Candida spp. were also diagnosed in one animal. Regarding sensitivity tests, the most efficient antibiotics were Gentamicin 54.5% (12/22) followed by Ciprofloxacin 50% (11/22), Enrofloxacin 45% (10/22), Neomycin 45% (10/22), Amikacin 45% (10/22), Cefoperazone 36% (8/22), Levofloxacin 31% (7/22), Norfloxacin 27% (6/22), Chloramphenicol 27% (6/22) and Cephalexin 22.7% (5/22). Likewise, the most resistant antibiotics in descending order were Streptomycin 95.4% (21/22), Penicillin and Cloxacillin 90.9% (20/22), Amoxicilin, Moxifloxacin and Ampicillin 86% (19/22), Oxytetracycline and Ceftriaxone 81.8% (18/22), Cephalexin 72.7% (16/22), Levofloxacillin 68% (15/22), Carbenicillin, Chloramphenicol, Kanamycin and Cefoperazone 63.6% (14/22), Tobramycin, Neomycin and Enrofloxacin 54.5% (12/22), Amikacin and Ciprofloxacin 50% (11/22), Cephotaxime 45.5 (10/22), Norfloxacin and Gentamycin 40.9% (9/22), Clindamycin and Septran 22.7% (5/22), Amoxiclav and Erythromycin 18 % (4/22). The present study concluded that the most prevalent microorganisms isolated from uterine discharge, were found to be resistant to beta-lactam antimicrobials as well, the study highlighted the significance of performing microbiological analyses as well as sensitivity tests prior to applying an antimicrobial therapy.